Factors Affecting Teachers’ Turnover: Basis for a Proposed Retention Program - Santiago, Noland; Santos, Teresita; Centeno, Ana Kristina Santiago (Future Science / FSH-PH Publications, 2022)
The significant role of education in human development is universally recognized. More than anybody else in the education sector, teachers play a vital role in the development of an individual. However, it becomes a tremendous struggle for the school administrators on how they can retain their teachers, especially those whose services are much needed. This study determined the possible factors that cause the high teachers' turnover, which can be used as a basis for the retention program among faculty members. Thirty-seven (37) teachers from three different schools were given a survey questionnaire to determine the factors that affected their decision to leave the academic institution. The descriptive research design was utilized for this study. The study yielded the following findings which showed why teachers decided to leave the school where they work. The personal factors were considered to a moderate extent, with the change of environment most impactful. Likewise, the institutional factors also affected the teachers’ turnover to a moderate extent, mostly because the opportunities for training are limited. Finally, the psychological factors got the least impact on the teachers’ turnover, with demoralization and insecurities they felt from colleagues as the very impactful. Based on the result of the study, a retention program was deemed necessary and was proposed by the researcher.